STRATEGI PEMBELAJARAN SENI TARI PERSEMBAHAN MELAYU RIAU DI SMAN 4 PEKAN BARU - Nikmatuz Zuhro Aminin; Syeilendra (Universitas Negeri Padang, 2025)
This research aims to provide an in-depth description of the learning strategies for Riau Malay Dance Performance applied by cultural arts teachers at SMAN 4 Pekanbaru, particularly in the XI Medical 3 class. This type of research is qualitative with a descriptive approach. Data collection techniques were conducted through literature study, observation, interviews, and documentation. The main instrument in this research is the researcher themselves, assisted by observation sheets, writing tools, and visual documentation devices. Data analysis was carried out by collecting data, identifying data, clarifying data, describing data, elaborating data, and drawing conclusions. The research results show that the learning strategies used by the teachers include three main stages: planning, implementation, and evaluation/assessment. At the planning stage, teachers prepare teaching modules based on the Independent Curriculum that is oriented towards learning objectives, methods, and media that align with the characteristics of the students. At the implementation stage, the teacher employs direct learning strategies with a student-centred approach, while combining several methods which begin with lectures, question and answer sessions, demonstrations, using imitation strategies demonstrated by the teacher based on the theory from the teaching material, so that students can learn dance movements progressively and contextually. In the learning process, the teacher facilitates students with supporting media such as dance videos, accompanying music, student worksheets, whiteboards, and props. The assessment is carried out diagnostically to draw out basic knowledge about the teaching material and formatively to see the achievement of learning objectives, covering aspects of movement techniques, expression, cohesion, and understanding the meaning of dance. As a follow-up, the teacher assigns students who have not reached the learning outcomes the task of creating a video of their practice of the Offering Dance.